YTHDF2-mediated m6A modification regulates mRNA stability of Immediate early response gene 3 to modulate cell death in Staphylococcus aureus-induced bovine mastitis - Yue Xing; Siyuan Mi; Siqian Chen; Xinyue Tao; Zihan Zhang; Yuanjun Shi; Xingping Wang; Ying Yu (Frontiers in Cellular and Infection Microbiology)
BackgroundStaphylococcus aureus (S. aureus)-induced bovine mastitis is a major challenge for dairy production, causing significant economic losses. The regulatory mechanisms underlying host cell apoptosis and inflammation during S. aureus infection remain unclear. Therefore, this study investigates the role of N6-methyladenosine (m6A) modification and its reader protein YTHDF2 in regulating mRNA stability, apoptosis, and inflammation in bovine mammary epithelial cells (Mac-T cells) under S. aureus challenge.MethodsMeRIP-seq, RIP-seq, and RT-qPCR were used to analyze m6A-modified IER3 mRNA and its interaction with YTHDF2. Apoptosis, necrosis, and mitochondrial function were assessed using YO-PRO-1/PI staining and JC-1 assays.ResultsS. aureus infection significantly downregulated YTHDF2 expression in Mac-T cells, leading to destabilization of m6A-modified IER3 mRNA. This resulted in increased reactive oxygen species (ROS) levels, mitochondrial dysfunction, and cell apoptosis. Overexpression of YTHDF2 restored mRNA stability, reduced apoptosis, and preserved mitochondrial function.ConclusionYTHDF2 regulates m6A-modified mRNA stability to modulate apoptosis and inflammation during S. aureus infection. These findings provide new insights into understanding the molecular mechanisms of bovine mastitis and provide genetic markers for breeding mastitis-resistant dairy cows.